Preparation method and application of porous carbon loaded iron-based catalyst

By using the self-assembly reaction of nitrogen-containing carbon-based ligands and cyclodextrins, a nitrogen-doped porous carbon catalytic material was prepared under high-speed iron load, which solved the problems of iron nanoparticle agglomeration and low metal load, and achieved efficient removal of polluted water phenolic pollutants have excellent selectivity and low temperature removal performance.

CN119236933APending Publication Date: 2025-01-03ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310810905.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Iron nanoparticles in existing nitrogen-doped porous carbon-supported iron catalytic materials are prone to agglomeration during high-temperature calcination, resulting in limited catalytic performance and low metal loading, making it difficult to effectively remove toxic organic pollutants in contaminated water.

Method used

A nitrogen-containing carbon-based ligand and cyclodextrin with a unique hydrophobic cavity were used for self-assembly reactions, and uniformly dispersed high-iron-supported catalytic material was prepared by hydrothermal and calcined treatment, and phenolic pollutants were selectively removed by hydrophobic interaction.

Benefits of technology

High dispersion and high loading of iron nanoparticles are achieved, catalytic performance is significantly improved, and it can efficiently remove phenolic pollutants under low temperature conditions, with excellent selectivity and low temperature removal performance, avoiding iron ions escape and iron-containing pollution Pile of mud.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004319640970000011
    Figure HDA0004319640970000011
  • Figure HDA0004319640970000012
    Figure HDA0004319640970000012
  • Figure HDA0004319640970000021
    Figure HDA0004319640970000021
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a porous carbon-loaded iron-based catalyst, and a nitrogen-doped porous carbon-loaded iron catalytic material is prepared by using the anchoring effect of nitrogen-containing carbon-based ligand 8-hydroxyquinoline and the spatial isolation effect of cyclodextrin containing a unique hydrophobic cavity through hydrothermal and calcination treatment. And high load (9.21 wt%-18.01 wt%) and high dispersion of the iron nanoparticles are realized. The method has the advantages that the problems that in a traditional iron-based catalyst, iron nanoparticles are prone to agglomeration, and the iron loading capacity is not high are solved, and the material has a good catalytic removal effect on toxic organic pollutants in wastewater and meanwhile has excellent selective removal performance on phenolic pollutants. The method disclosed by the invention is simple and easy to implement, low in raw material cost, good in controllability and reproducibility and easy to practically develop.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a catalyst, and in particular to a method for preparing a porous carbon-loaded iron catalytic material for removing organic pollutants in polluted water and its application, belonging to the field of chemistry and environmental governance. Background Art

[0002] With the rapid development of modern industry and agriculture, a large number of toxic organic pollutants have been found in the water environment, posing a serious threat to the ecological environment and human health. Advanced oxidation processes based on reactive oxygen species (ROSs-AOPs) are considered to be one of the most effective technologies for removing toxic organic pollutants. The key to this process is to activate oxidants such as permonosulfate (PMS) and hydrogen peroxide (H2O2) in a certain way to produce reactive oxygen species, which further attack pollutants to form non-toxic and harmless small molecule compounds. At present, oxidants can be activated by ultraviolet irradiation, heating, ultrasound and transition metals. Among them, the transition metal activation method is considered to be an ideal choice because of its mild reaction conditions and no need for additional energy input. Among transition metals, iron-based catalysts have been widely studied due to their advantages such as low cost, high reserves and low toxicity.

[0003] Among transition metal iron-based catalysts, nitrogen-doped porous carbon-supported iron catalytic materials (Fe@NC) are favored by researchers because of their carbon shell that can protect the metal from passivation and overflow, and the doped nitrogen that can significantly accelerate the electron transfer between the catalyst and the oxidant. Their catalytic performance is highly dependent on the size and density of the metal active centers. Most of the synthesis methods reported so far for Fe@NC catalysts mainly involve high-temperature pyrolysis of complexes formed by iron salts and N- and C-containing precursors such as pyridine, phthalocyanine, imidazole, and porphyrin. However, iron nanoparticles (NPs) tend to agglomerate during high-temperature calcination, which will seriously hinder the exposure of metal active sites and further limit the improvement of activity. Therefore, it is a difficult task to propose a new method to prepare Fe@NC catalytic materials to reduce the agglomeration of iron nanoparticles.

[0004] So far, many methods have been proposed at home and abroad to reduce the agglomeration of iron NPs in Fe@NC materials, such as Publication No.: CN115799539A "A nitrogen-doped porous carbon-supported Fe single-atom material and its preparation method and application" uses zeolite imidazole framework (ZIF-8) to load ferrocene, which greatly promotes the dispersion of iron NPs. Publication No.: CN108579783B "A method for preparing a nitrogen-doped porous carbon-supported metal single-atom material" uses polymerization reactions such as amino Schiff base reaction to polymerize porphyrin and metal porphyrin, effectively inhibiting the agglomeration of iron NPs during high-temperature calcination. However, the above methods involve the use of a large amount of polar solvents, which is not conducive to the protection of the ecological environment. In addition, the metal loading of the catalysts prepared by these methods is relatively low (less than 4wt%), resulting in limited catalytic performance of Fe@NC materials. Summary of the invention

[0005] In order to solve the problem that iron NPs in the existing nitrogen-doped porous carbon-supported iron catalytic materials for removing toxic organic pollutants from wastewater are easy to agglomerate during high-temperature calcination and the metal loading in the catalyst is low, the present invention provides a preparation method and application of a porous carbon-supported iron catalytic material, the preparation method innovatively utilizes the anchoring effect of nitrogen-containing carbon-based ligands and the spatial isolation effect of cyclodextrin containing unique hydrophobic cavities to prepare a uniformly dispersed catalytic material with a high iron loading, the catalytic material can effectively activate oxidants such as peroxymonosulfate to produce active oxygen species, and achieve efficient removal of toxic organic pollutants in polluted water. In addition, the prepared catalytic material has strong hydrophobicity, and can selectively remove phenolic organic pollutants based on the hydrophobic interaction between the catalytic material and the pollutant. The present invention opens up a new way to effectively construct a uniformly dispersed Fe@NC high-metal-loaded catalyst for selectively removing toxic organic pollutants.

[0006] A method for preparing a porous carbon-supported iron-based catalyst, the specific steps of which are as follows:

[0007] (1) A suitable cyclic structure material having a unique hydrophobic cavity and a hydrophobic nitrogen-containing carbon-based ligand 8-hydroxyquinoline are placed in an aqueous solution at a certain molar ratio and stirred to undergo a self-assembly reaction to obtain a uniform inclusion complex solution.

[0008] (2) Adding iron salt to the mixed solution of step (1), transferring the solution to a polytetrafluoroethylene liner for hydrothermal treatment after stirring, centrifuging the obtained suspension and drying it in a vacuum oven to obtain a black powder.

[0009] (3) The black powder obtained in step (2) is placed in a tubular furnace, nitrogen is introduced into the furnace, and calcined to obtain a nitrogen-doped porous carbon-supported iron catalytic material.

[0010] Preferably, the cyclic structure substance with a unique hydrophobic cavity in step (1) is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, with a concentration of 0.015-0.021 mol / L; the hydrophobic nitrogen-containing carbon-based ligand is 8-hydroxyquinoline; the molar ratio is 1:1-3, the stirring speed is 400-600r / min; and the stirring time is 8-14h. More preferably, the stirring time is 10-12h. The preferred stirring conditions are conducive to the full self-assembly of cyclodextrin and 8-hydroxyquinoline in aqueous solution, which is conducive to the subsequent anchoring of metals and the isolation of complexes.

[0011] Preferably, the iron salt in step (2) is one of ferric nitrate nonahydrate, ferric sulfate hydrate and ferric chloride hexahydrate; the stirring time is 4-14 hours, and more preferably, the stirring time is 6-12 hours. The preferred stirring conditions are conducive to the combination of 8-hydroxyquinoline and iron ions in the cyclodextrin cavity, which is conducive to the anchoring and dispersion of iron NPs.

[0012] Preferably, in step (2), the hydrothermal treatment temperature is 140-240°C, the hydrothermal treatment time is 4-12 hours, the drying temperature is 60-80°C, and the drying time is 8-24 hours. More preferably, the hydrothermal treatment temperature is 160-240°C, the hydrothermal treatment time is 4-8 hours, the drying temperature is 60-80°C, and the drying time is 8-14 hours.

[0013] Preferably, the calcination process described in step (3) is to heat the temperature from room temperature to 300°C at a heating rate of 5°C / min, and keep the temperature for 2 hours; then continue to heat the temperature to 700-900°C at a heating rate of 5°C / min, and keep the temperature for 2 hours.

[0014] The invention discloses an application of a porous carbon-supported iron-based catalyst, which is applicable to a method for preparing a nitrogen-doped porous carbon-supported iron catalytic material, and is characterized in that: a nitrogen-doped porous carbon-supported iron catalytic material with a dosage of 1-5000 mg / L and an oxidant with a concentration of 10-8000 mg / L are added to polluted wastewater, and the mixture is fully stirred. The mixture is reacted for 2-30 minutes at a temperature of 10-80°C and a pH value of 2-10 to selectively remove phenol pollutants with a concentration of 0.001-30000 μg / L in the polluted water.

[0015] The oxidant is one or more of permonosulfate (PMS), persulfate (PS), or hydrogen peroxide (H2O2), wherein the permonosulfate is one or more of sodium permonosulfate (NaHSO5), potassium permonosulfate (KHSO5), or ammonium permonosulfate (NH4HSO5), and the persulfate is one or more of sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), or ammonium persulfate ((NH4)2S2O8).

[0016] The phenolic pollutants in the wastewater are one or more of 4-chlorophenol (4-CP), 2,4,6-trichlorophenol (TCP), thymol (TM), 3-methoxyphenol (3-MOP), p-cresol (pC) and 5-chloro-2-(2,4-dichlorophenoxy)phenol (5-ClDP).

[0017] Preferably, the amount of the nitrogen-doped porous carbon-loaded iron catalytic material is 10-2000 mg / L, and the amount of the oxidant is preferably 20-4000 mg / L, ensuring that the dosage of the nitrogen-doped porous carbon-loaded iron catalytic material and the oxidant is within this range, which can selectively remove phenol pollutants in polluted water.

[0018] Preferably, the concentration of phenol pollutants in the polluted water body is 0.005-30000 μg / L, ensuring that this concentration is conducive to the selective removal of phenol pollutants in the polluted water body.

[0019] Preferably, the reaction temperature is 20-70°C.

[0020] Preferably, the pH value of the solution during the reaction is 2-10.

[0021] Compared with the prior art, the present invention has the following beneficial results:

[0022] 1. The present invention utilizes the anchoring effect of the hydrophobic carbon-based ligand 8-hydroxyquinoline and the isolation effect of the ring-shaped structure material with a unique hydrophobic cavity to prepare a nitrogen-doped porous carbon-supported iron catalytic material through hydrothermal and calcination treatment, thereby achieving high loading (9.21-18.01wt%) and high dispersion of iron nanoparticles.

[0023] 2. The nitrogen-doped porous carbon-loaded iron catalytic material described in the present invention can selectively remove phenolic pollutants based on the hydrophobic interaction between the catalytic material and the pollutants, and can maintain efficient removal of phenolic pollutants under zero-degree conditions, and has excellent selective removal ability and low-temperature removal performance.

[0024] 3. When the nitrogen-doped porous carbon-supported iron catalytic material of the present invention removes toxic organic pollutants, the escape of iron ions is small during the reaction process, which effectively avoids the accumulation of iron-containing sludge. The entire reaction system has high catalytic activity and a wide pH application range, which is conducive to the development of practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the porous carbon-supported iron-based catalyst prepared in Example 1;

[0026] Figure 2 TEM image of the porous carbon-supported iron-based catalyst prepared in Example 1;

[0027] Figure 3 is the XRD pattern of the porous carbon-supported iron-based catalyst prepared in Example 1;

[0028] Figure 4 This is a water contact angle diagram of the porous carbon-supported iron-based catalyst prepared in Example 1;

[0029] Figure 5 This is a diagram showing the removal effect of the porous carbon-supported iron-based catalyst prepared in Example 1 on the toxic organic pollutant 4-chlorophenol.

[0030] Figure 6 This is a diagram showing the removal effect of the porous carbon-supported iron-based catalyst prepared in Example 1 for selectively removing phenolic pollutants.

[0031] Figure 7 This is the synthesis principle diagram of this application. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific examples. These implementation cases are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0033] Embodiment 1:

[0034] 1 g of β-cyclodextrin and 0.2558 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0035] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 6 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0036] The black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept at that temperature for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept at that temperature for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material (β-Fe@NC).

[0037] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is shown in FIG. Figure 1 As shown in the figure, β-Fe@NC presents spherical nanoparticles of uniform size, with a particle size of about 400 nm. After testing, the specific surface area of ​​β-Fe@NC prepared in this example is 330.97 m 2 / g, pore volume is 0.4295cm 3 / g.

[0038] The TEM image of the porous carbon-supported iron-based catalyst prepared in this example is shown in FIG. Figure 2 As shown, it can be seen that β-Fe@NC exhibits uniformly dispersed iron nanoparticles with an average particle size of 20 nm. According to the test, the iron loading in the β-Fe@NC prepared in this embodiment is 16.33 wt%.

[0039] The XRD spectrum of the porous carbon-supported iron-based catalyst prepared in this example is shown in Figure 3 As shown (catalytic material Fe@NC containing a single 8-hydroxyquinoline iron complex calcined). It can be seen that the graphite carbon peak and zero-valent iron peak of β-Fe@NC are stronger, which indicates that the introduction of β-cyclodextrin promotes the formation of graphite carbon and zero-valent iron, which is beneficial to improve the ability of the catalytic material to activate PMS.

[0040] The water contact angle picture of the porous carbon-supported iron-based catalyst prepared in this example is shown in Figure 4 As shown, it can be seen that the catalytic material has good hydrophobicity.

[0041] The removal effect of the porous carbon-supported iron-based catalyst prepared in this example on the toxic organic pollutant 4-chlorophenol is shown in the figure. Figure 5 As shown, the catalytic material (100 mg / L) can remove 99.9% of 4-chlorophenol (13000 μg / L) within 25 minutes after activating PMS (300 mg / L) at 25°C and pH 6.8. The test shows that the catalytic material has a high catalytic activity.

[0042] The removal effect of the porous carbon-supported iron-based catalyst prepared in this example on phenol pollutants with different hydrophobicity is shown in the figure below. Figure 6 As shown. It can be seen that the catalytic material can selectively remove phenolic pollutants based on the hydrophobic interaction between itself and the pollutants, and the more hydrophobic the pollutants are, the easier they are to be removed.

[0043] Embodiment 2:

[0044] 1 g of β-cyclodextrin and 0.1279 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0045] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 6 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0046] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0047] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similarly, after testing, the iron loading in the catalytic material prepared in this embodiment is 9.21wt%. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 Similarly, the characteristic diffraction peaks of graphite carbon and zero-valent iron also appeared, indicating that the sample was successfully prepared. The water contact angle image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 4 The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant thymol is similar to Figure 5 Similarly, the catalytic material (100 mg / L) activated PMS (300 mg / L) at 25°C and pH 6.8 and removed 93.4% of thymol (15000 μg / L) within 25 min. Figure 6 similar.

[0048] Embodiment 3:

[0049] 1 g of β-cyclodextrin and 0.3836 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0050] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 6 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0051] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0052] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similarly, after testing, the iron loading in the catalytic material prepared in this embodiment is 18.01wt%. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 The water contact angle image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant 2,4,6-trichlorophenol is shown in Figure 1. Figure 5 Similarly, the catalytic material (100 mg / L) can remove 99.9% of 2,4,6-trichlorophenol (20000 μg / L) within 25 min after activating PMS (300 mg / L) at 25°C and pH 6.8. Figure 6 similar.

[0053] Embodiment 4:

[0054] 1 g of β-cyclodextrin and 0.2558 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0055] 0.5 g of Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 180°C and a hydrothermal time of 6 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0056] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0057] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similarly, after testing, the iron loading in the β-Fe@NC prepared in this embodiment is 15.73wt%. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 Similar, but the characteristic diffraction peak intensity of zero-valent iron is slightly reduced, which indicates that the hydrothermal temperature is lower than the reduction of the metal during the hydrothermal process. Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant 2,4,6-trichlorophenol is shown in Figure 1. Figure 5 Similarly, the catalytic material (100 mg / L) can remove 99.9% of 2,4,6-trichlorophenol (20000 μg / L) within 25 min after activating PMS (300 mg / L) at 25°C and pH 6.8. Figure 6 similar.

[0058] Embodiment 5:

[0059] 1 g of β-cyclodextrin and 0.2558 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0060] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 240°C and a hydrothermal time of 6 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0061] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0062] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similar to the above, but the particle size of the iron nanoparticles is larger, which indicates that too high a hydrothermal temperature will also cause agglomeration of the iron nanoparticles; after testing, the iron loading in the catalytic material prepared in this embodiment is 16.55wt%. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 The water contact angle image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant 4-chlorophenol is shown in FIG. Figure 5 Similarly, the catalytic material (100 mg / L) activated PMS (300 mg / L) at 25°C and pH 6.8 and removed 92.5% of 4-chlorophenol (13000 μg / L) within 25 min. Figure 6 similar.

[0063] Example 6

[0064] 1 g of α-cyclodextrin and 0.2984 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0065] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 6 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0066] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0067] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similarly, after testing, the iron loading in the catalytic material prepared in this embodiment is 16.87 wt %. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 The water contact angle image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant 5-chloro-(2,4-dichlorophenoxy)phenol is shown in Figure 1. Figure 5 Similarly, the catalytic material (100 mg / L) activated PMS (300 mg / L) at 25°C and pH 6.8 and removed 99.9% of 5-chloro-2-(2,4-dichlorophenoxy)phenol (30000 μg / L) within 25 min. Figure 6 similar.

[0068] Embodiment 7:

[0069] 1 g of γ-cyclodextrin and 0.2238 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0070] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 6 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0071] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0072] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similarly, after testing, the iron loading in the catalytic material prepared in this embodiment is 15.66wt%. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 The water contact angle image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant 2,4,6-trichlorophenol is shown in Figure 1. Figure 5 Similarly, the catalytic material (100 mg / L) activated PMS (300 mg / L) at 25°C and pH 6.8 and removed 98.8% of 2,4,6-trichlorophenol (20000 μg / L) within 25 min. Figure 6 similar.

[0073] Embodiment 8:

[0074] 1 g of β-cyclodextrin and 0.2558 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0075] 0.5 g of Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 4 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0076] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0077] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similarly, after testing, the iron loading in the catalytic material prepared in this embodiment is 13.27wt%. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 Similar, but the characteristic diffraction peak intensity of graphite carbon and zero-valent iron is slightly reduced, which indicates that too short hydrothermal time is not conducive to the reduction of metal and the formation of graphite carbon. Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant thymol is shown in Figure 1. Figure 5 Similarly, the catalytic material (100 mg / L) activated PMS (300 mg / L) at 25°C and pH 6.8 and removed 85.2% of thymol (15000 μg / L) within 25 min. Figure 6 similar.

[0078] Embodiment 9:

[0079] 1 g of β-cyclodextrin and 0.2558 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0080] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 8 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0081] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 900°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0082] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to that of the porous carbon-supported iron catalytic material prepared in this embodiment. Figure 3 The water contact angle image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant 4-chlorophenol is shown in FIG. Figure 5 Similarly, the catalytic material (100 mg / L) activated PMS (300 mg / L) at 25°C and pH 6.8 and removed 89.9% of 4-chlorophenol (13000 μg / L) within 25 min. Figure 6 similar.

[0083] Embodiment 10:

[0084] 1 g of β-cyclodextrin and 0.2558 g of 8-hydroxyquinoline were added to a beaker containing 50 mL of deionized water, and the speed of the magnetic stirrer was adjusted to 500 r / min and the stirring time was 12 h to obtain a uniform inclusion complex solution.

[0085] 0.5 g Fe(NO3)3·9H2O was added to the inclusion complex solution, and then placed on a magnetic stirrer with the rotation speed adjusted to 500 r / min and the stirring time was 12 h. The obtained mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment at a hydrothermal temperature of 220°C and a hydrothermal time of 8 h. The obtained suspension was centrifuged and placed in a vacuum oven for drying to obtain a black powder.

[0086] The above-mentioned black powder was placed in a tubular furnace for calcination, with the temperature rising from room temperature to 300°C at a heating rate of 5°C / min and kept warm for 2 hours, and then continued to rise to 700°C at a heating rate of 5°C / min and kept warm for 2 hours, finally obtaining a nitrogen-doped porous carbon-loaded iron catalytic material.

[0087] The SEM image of the porous carbon-supported iron-based catalyst prepared in this example is Figure 1 The TEM image of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example is similar to Figure 2 Similarly, after testing, the iron loading in the catalytic material prepared in this embodiment is 15.45wt%. The XRD spectrum of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this embodiment is similar to Figure 3 Similar, but the characteristic diffraction peak intensity of graphite carbon and zero-valent iron is slightly reduced, which indicates that the second stage pyrolysis temperature is too low and is not conducive to the formation of graphite carbon and zero-valent iron. Figure 4 Similarly, the catalytic material also has obvious hydrophobicity. The removal effect of the nitrogen-doped porous carbon-supported iron catalytic material prepared in this example on the toxic organic pollutant 4-chlorophenol is shown in FIG. Figure 5 Similarly, the catalytic material (100 mg / L) activated PMS (300 mg / L) at 25°C and pH 6.8 and removed 88.2% of 4-chlorophenol (13000 μg / L) within 25 min. Figure 6 similar.

[0088] The above are only some embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments, and does not represent all technical solutions under the concept of the present invention. It should be pointed out that for those skilled in the art, any additions and modifications inspired by the concept of this patent and specific implementation cases without departing from the principle of the present invention, such as non-substantial changes such as determining different catalyst and oxidant dosages and different temperatures according to different wastewater and pollutant concentrations, should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon-supported iron-based catalyst, characterized in that: The steps include: (1) placing a cyclic structure substance having a hydrophobic cavity and 8-hydroxyquinoline in a certain molar ratio in an aqueous solution and stirring them to generate a self-assembly reaction to obtain a uniform inclusion complex solution; the cyclic structure substance having a hydrophobic cavity is one of α-cyclodextrin, β-cyclodextrin, or γ-cyclodextrin; (2) adding iron salt to the inclusion compound solution of step (1), transferring the solution to a polytetrafluoroethylene liner for hydrothermal treatment after stirring, centrifuging the obtained suspension and placing it in a vacuum oven for drying to obtain a black powder; (3) The black powder obtained in step (2) is placed in a tubular furnace, nitrogen is introduced, and calcined to obtain a porous carbon-supported iron catalytic material.

2. The method for preparing a porous carbon-supported iron-based catalyst according to claim 1, characterized in that: The concentration of the hydrophobic cavity ring structure substance in step (1) is 0.015-0.021 mol / L; the molar ratio of the hydrophobic cavity ring structure substance to 8-hydroxyquinoline is 1:1-3; the stirring speed is 400-600 r / min, and the stirring time is 8-14 h.

3. The method for preparing a porous carbon-supported iron-based catalyst according to claim 1, characterized in that: The iron salt described in step (2) is one of ferric nitrate nonahydrate, ferric sulfate hydrate, or ferric chloride hexahydrate.

4. The method for preparing a porous carbon-supported iron-based catalyst according to claim 3, characterized in that: The iron salt concentration is 5-10 g / L, and the stirring time is 4-14 h; the hydrothermal treatment temperature is 140-240° C., and the hydrothermal treatment time is 4-8 h; the drying temperature is 60-80° C., and the drying time is 8-14 h.

5. The method for preparing a porous carbon-supported iron-based catalyst according to claim 1, characterized in that: The calcination temperature in step (3) is raised from room temperature to 300° C. for 2 hours; then raised to 700-900° C. for 2 hours.

6. The method for preparing a porous carbon-supported iron-based catalyst according to claim 5, characterized in that: The calcination temperature of 300°C is reached by heating from room temperature at a heating rate of 5°C / min; the heating to 700-900°C is reached at a heating rate of 5°C / min.

7. Use of a porous carbon-supported iron-based catalyst prepared according to claims 1-4, characterized in that: 1-5000 mg / L of highly active nitrogen-doped porous carbon-supported iron catalytic material and 10-8000 mg / L of an oxidant are added to a water body containing phenol pollutants, and the mixture is fully stirred. The mixture is reacted for 2-30 minutes at a temperature of 10-80°C and a pH value of 2-10 to selectively remove phenol pollutants with a concentration of 0.001-30000 μg / L in the polluted water body.

8. The use of a porous carbon-supported iron-based catalyst according to claim 7, characterized in that: The oxidant is one or more of peroxymonosulfate, persulfate, or hydrogen peroxide, and the phenolic pollutants are one or more of 4-chlorophenol (4-CP), 2,4,6-trichlorophenol (TCP), thymol (TM), 3-methoxyphenol (3-MOP), p-cresol (pC), or 5-chloro-2-(2,4-dichlorophenoxy)phenol (5-ClDP).

Citation Information

Cited By

  • Carbonized polydopamine coated iron oxide as well as preparation method and application thereof

    CN122059450A

  • A carbonized polydopamine-coated iron oxide and a preparation method and application thereof

    CN122059450B